The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/mec.14705
|View full text |Cite
|
Sign up to set email alerts
|

Genomic signatures of fine‐scale local selection in Atlantic salmon suggest involvement of sexual maturation, energy homeostasis and immune defence‐related genes

Abstract: Elucidating the genetic basis of adaptation to the local environment can improve our understanding of how the diversity of life has evolved. In this study, we used a dense SNP array to identify candidate loci potentially underlying fine-scale local adaptation within a large Atlantic salmon (Salmo salar) population. By combining outlier, gene-environment association and haplotype homozygosity analyses, we identified multiple regions of the genome with strong evidence for diversifying selection. Several of these… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
103
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(127 citation statements)
references
References 120 publications
(221 reference statements)
8
103
0
Order By: Relevance
“…In Atlantic salmon, two genomic regions on chromosomes 9 and 25 have been shown to have a disproportionate influence on life history strategy and population differentiation within and among populations (Ayllon et al 2015, Barson et al 2015, Czorlich et al 2018, Pritchard et al 2018, Aykanat et al 2019). The so-called vgll3 and six6 genomic regions are named after the most prominent genes in their respective haploblocks on chromosomes 25 and 9, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In Atlantic salmon, two genomic regions on chromosomes 9 and 25 have been shown to have a disproportionate influence on life history strategy and population differentiation within and among populations (Ayllon et al 2015, Barson et al 2015, Czorlich et al 2018, Pritchard et al 2018, Aykanat et al 2019). The so-called vgll3 and six6 genomic regions are named after the most prominent genes in their respective haploblocks on chromosomes 25 and 9, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the outliers we detected were localized to a 250 Kb region of chromosome 9 that has previously been implicated in important life history variation for this species. In European Atlantic salmon, a particular a gene in this region, six6, has been associated with age-at-maturity in Atlantic salmon in Europe (Barson et al, 2015;Johnston et al, 2014), differences in run-timing within rivers, and local adaptation between tributaries (Cauwelier et al, 2017;Pritchard et al, 2018). Our study is the first to report direct evidence of within-river variation at this locus in a North American population of Atlantic salmon.…”
Section: Adaptive Variationmentioning
confidence: 60%
“…Clearly more work is needed to link genomic variation with important phenotypic and life history variation in this system. In Europe, Pritchard et al (Pritchard et al, 2018) found an association of the six6 locus with a variable explaining "flow volume" for Atlantic salmon in the Teno/Tana River in Norway. Our results for a North American system thus suggest that stream parameters related to river size (flow volume and velocity) that differ between upper and lower reaches of large river systems may be mechanisms driving convergent local adaptations across continents and represents avenues for future study in relation to known differences in morphology and life history.…”
Section: Adaptive Variationmentioning
confidence: 97%
See 1 more Smart Citation
“…Sampled fish were captured in the last four weeks of the fishing season, in August (two to four weeks after most individuals have entered the river), to minimize the number of fish from tributary and headwater populations (Erkinaro et al, 2010). Using the abovementioned dataset, Aykanat et al (2015) identified two subpopulations that have been subsequently identified to represent the Teno mainstem (Tenojoki, referred to as sub-population 1 and Inarijoki (sub-population 2) sub-populations (Pritchard et al, 2018).…”
Section: Sample Collectionmentioning
confidence: 99%